Fishing in the Cold War: Canada, Newfoundland and the International Politics of the Twelve-Mile Fishing Limit, 1958-1969 - Wright, Miriam (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1997)
AbstractThe intensification of offshore fishing by European trawlers in the northwest Atlantic in the 1950s and 1960s had many repercussions for the Newfoundland fishery. With only a three-mile fishing limit between themselves and the more technologically advanced Europeans, many people involved in the Newfoundland fishery demanded the federal government extend fishing rights to twelve miles from shore. The international debate on the extended fishing rights/territorial waters issue, however, was complicated by its entanglement in Cold War politics. Indeed, the Canadian government's attempts to find a solution in the aftermath of the failed United Nations Law of the Sea Conferences in 1958 and 1960 came face-to-face with the defence agenda of the United States Navy. In such an atmosphere, the Canadian government could do little to protect the resource without risking the wrath of its neighbour and largest trading partner.